2018
DOI: 10.1007/s00442-018-4137-z
|View full text |Cite
|
Sign up to set email alerts
|

Niche opportunities for invasive annual plants in dryland ecosystems are controlled by disturbance, trophic interactions, and rainfall

Abstract: Resource availability and biotic interactions control opportunities for the establishment and expansion of invasive species. Studies on biotic resistance to plant invasions have typically focused on competition and occasionally on herbivory, while resource-oriented studies have focused on water or nutrient pulses. Through synthesizing these approaches, we identify conditions that create invasion opportunities. In a nested fully factorial experiment, we examined how chronic alterations in water availability and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 49 publications
(16 citation statements)
references
References 58 publications
0
16
0
Order By: Relevance
“…For plants with roots in the ground, competition may complicate responses to the different physical effects (shading, reflection, and infrared radiation emission) of the rain-out shelter infrastructure (Concilio, Nippert, Ehrenfeucht, Cherwin, & Seastedt, 2016). For example, some studies have found interactions of disturbance or trophic relationships (Gill et al, 2018) or soil invertebrates (Johnson, Staley, McLeod, & Hartley, 2011) with drought. Additionally, soil microbial communities may be affected by changes in soil temperature in addition to moisture under rain-out shelters (Cable et al, 2011;Ochoa-Hueso et al, 2018), but we used sterilized soil so this may not be an issue for our potted plants.…”
Section: Discussionmentioning
confidence: 99%
“…For plants with roots in the ground, competition may complicate responses to the different physical effects (shading, reflection, and infrared radiation emission) of the rain-out shelter infrastructure (Concilio, Nippert, Ehrenfeucht, Cherwin, & Seastedt, 2016). For example, some studies have found interactions of disturbance or trophic relationships (Gill et al, 2018) or soil invertebrates (Johnson, Staley, McLeod, & Hartley, 2011) with drought. Additionally, soil microbial communities may be affected by changes in soil temperature in addition to moisture under rain-out shelters (Cable et al, 2011;Ochoa-Hueso et al, 2018), but we used sterilized soil so this may not be an issue for our potted plants.…”
Section: Discussionmentioning
confidence: 99%
“…Global environmental changes are likely to accelerate plant invasions (Dukes and Mooney 1999 ; Theoharides and Dukes 2007 ; Bradley et al 2012 ), although the contraction of geographical range can also be projected for some recent invasive species (Bradley et al 2009 ). Despite the intense research on the effects of climate change drivers on community invasibility and the success of invasive species, responses to precipitation changes have not been fully understood (Smith et al 2000 ; Walther et al 2009 ; Pfeifer-Meister et al 2016 ; Thomason and Rice 2017 ; Gill et al 2018 ). To improve our knowledge in this field is particularly important in arid and semiarid ecosystems, where water availability has a prominent role in determining plant diversity, primary production, and community stability (Rutherford 1980 ; Bai et al 2004 ; Seddon et al 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…First, unlike chronosequence data, direct observation data are not confounded by space-for-time substitutions. For example, differences in community composition among fields can ‘mask’ within-community changes over time in chronosequence datasets [10, 23–24]. Second, shorter-term, direct observation data are more likely to detect short-term linear patterns, even if longer-term patterns are non-linear.…”
Section: Discussionmentioning
confidence: 99%
“…Traditional ecological theory suggests that without continued disturbances late-successional species will gradually replace these invaders [35]. Yet, in some, particularly semi-arid areas, early-successional, non-native species persist for decades or longer as potentially alternative-state communities [610]. Nonequilibrium ecology and resilience theory suggest that disturbances can induce a shift to community types that vary over time but resist returning to a pre-disturbance condition [11, 12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation